Pechini sol-gel synthesis of Ni(II) doped LiMnBO3/Li2MnO3/Li2B2O4 nano-photocatalyst under UV–Vis irradiation. (8th March 2021) - Ranjeh, Mahdi; Masjedi-Arani, Maryam; Amiri, Omid; Salavati-Niasari, Masoud
Abstract: NiO doped LiMnBO3 /Li2 MnO3 /Li2 B2 O4 (LMBO) nanoscale composites were prepared through sol-gel (Pechini-type) route using the combination of Ni, Mn and Li cations with Ethylenediaminetetraacetic acid (EDTA) as a chelating operator. By changing molar ratios of M: ethylene glycol: EDTA can control appearance properties of nanocomposites. Analyses of FT-IR, XRD and EDX were accomplished aimed at the approval of crystalline and structural features. Also, in order to investigation of morphology, scanning and transmission electron microscopy images were taken. The prepared nanocomposite with 1:1:1 M ratio in presence of EDTA has optimized size and morphology. Optical property and band-gap energy of NiO doped LMBO ternary nanocomposite computed by UV–Vis information is 3.1 eV. The magnetic character of the prepared nanocomposite investigated through VSM illustrates ferromagnetic performance. Besides, photodegradation activities of pristine and NiO doped LMBO ternary nanocomposites were examined by different lights on two diverse dyes of malachite green and acid red 88. Some operative factors including radiation, pollutant and nanoscale composite sort were considered in order to optimize elimination of water contaminant dyes. In both cationic and anionic dyes, NiO doped LMBO ternary nanocomposite has better performance than LMBO nanocomposite. Highlights: NiO doped Li-rich nanocomposite was used as a nano-photocatalyst. The photocatalyst nanocomposites were synthesized via modified pechini sol-gel approach. The optimal nanocomposite was obtained with changing of experimental conditions. Divers parameters were evaluated in order to higher photocatalytic efficiency. Optical and magnetic properties of nanocomposites were considered.